2020
DOI: 10.3390/nu12123787
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Cameroonian Plants Exhibit Anti-Inflammatory Activity in Human Gastric Epithelial Cells

Abstract: In Cameroon, local plants are traditionally used as remedies for a variety of ailments. In this regard, several papers report health benefits of Cameroonian spices, which include antioxidant and anti-microbial properties, whereas gastric anti-inflammatory activities have never been previously considered. The present study investigates the antioxidant and anti-inflammatory activities of hydro-alcoholic extracts of eleven Cameroonian spices in gastric epithelial cells (AGS and GES-1 cells). The extracts showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 41 publications
4
29
0
Order By: Relevance
“…Among the 11 tested extracts, four (A. melegueta, D. glomerata, T. tetraptera and E. giganteus) were effective in significantly reducing (−29/−43%) IL-6 release. T. tetraptera, and D. glomerata were also found to similarly reduce IL-6 release by GES-1 gastric epithelial cells [6]. In addition, four spice extracts (X. parviflora, X. aethiopica, M. myristica, and Z. leprieurii) were able to reduce (−21/−36%) IL-8 release, whereas this was markedly increased by D. glomerata and A. citratum.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Among the 11 tested extracts, four (A. melegueta, D. glomerata, T. tetraptera and E. giganteus) were effective in significantly reducing (−29/−43%) IL-6 release. T. tetraptera, and D. glomerata were also found to similarly reduce IL-6 release by GES-1 gastric epithelial cells [6]. In addition, four spice extracts (X. parviflora, X. aethiopica, M. myristica, and Z. leprieurii) were able to reduce (−21/−36%) IL-8 release, whereas this was markedly increased by D. glomerata and A. citratum.…”
Section: Discussionmentioning
confidence: 82%
“…Preliminary experiments were conducted to assess the effect of 11 Cameroonian spice extracts on the viability of differentiated SW 872 cells by MTS assay and morphological analysis. The extraction protocol, molecular composition, and potential cytotoxic effects in other cell lines of the spice extracts used in this study have been previously reported [5][6][7]. The MTS assay was conducted after treatment with different concentrations (1-100 µg/mL) of extracts for 24 h and 48 h. Viability threshold was set at 80% [15].…”
Section: Spice Extracts Up To 25 µG/ml Do Not Affect Sw 872 Cell Viability and Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Additional anti-inflammatory effects were recorded, including a significant decrease in IL-6 levels at 250 μg / mL and 500 μg / mL and a significant inhibition of lipoxygenase at concentrations ranging from 16 μg / mL to 250 μg / mL [ 39 ]. Also, pro-inflammatory mediators such as IL-8, IL-6 and the enzyme cyclo-oxygenase 2 (PTGS2) (COX-2) were significantly inhibited [ 40 ]. It is demonstrated that the anti-inflammatory activity of A .…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is an excellent target for evaluating the anti-inflammatory activity of various molecules, including those of plant origin. In fact, several classes of polyphenols can inhibit the action of this transcription factor in different cellular models [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%